Integration of mobile sensors in a telemedicine hospital system: remote-monitoring in COVID-19 patients - Muller, Alexander; Haneke, Hannah; Kirchberger, Valerie; Mastella, Giulio; Dommasch, Michael; Merle, Uta; Heinze, Oliver; Siegmann, Adonia; Spinner, Christoph; Buiatti, Alessandra; Laugwitz, Karl-Ludwig; Schmidt, Georg; et al. (Journal of Public Health, 2022)
Aim: The goal is to design and, in a next step, establish a scalable, multi-center telemonitoring platform based on existing systems for monitoring COVID-19 patients in home quarantine. In particular, the focus will be on raw data acquisition, integration of sensor data into the hospital system, structured data storage, and interoperability. Subject and methods: Data necessary for monitoring, otherwise provided in various portals, will be continuously queried and integrated into the hospital system via a new interface in this proof-of-concept work. Results: Based on extensive preliminary work at Klinikum rechts der Isar with a structured clinical database, we extend our system’s integration of raw data and visualization in dashboards, as well as scientific provision of data from mobile sensors for monitoring patients in home quarantine. Conclusion: Based on existing integrated telemonitoring systems supporting semantic and syntactic interoperability, short-term provision of scientific databases is possible. The integration of different mobile sensors into a clinical system for remote monitoring of patients around the clock is still new and to our knowledge unique.
CRIS-Team Scopus Importer:2023-03-08
Keywords: COVID-19; Digital health; Interoperability; Mobile sensors; Pandemic management; Remote-monitoring; Telemedicine; Wearables